Defining sports training. Vain ambition or necessity? - Bellotti, P. (EWF Scientific Magazine, 2015)
A trainer must ensure that in his definition of training there is: - a wide-ranging and well-structured process; o a phenomenon that comes about in its own time (which cannot be influenced); - an educational approach (with its various aspects); o complexity (constitutive and interpretive). The same complexity as indicated in the "science of complexity"; - a connection to the motor skills history of the individual, which means understanding the legacy, the personality, the vital action of the environment, the individual responses of each athlete, the consequent indulging the aptitudes and individualisation of the approach; - a practical approach that uses physical exercise to perfect the movement; - trial and error to measure the physical exercise and its effects; - the practical aspect (even if of uncertain interpretation) of the so-called parameters of the workload; - the professional code of conduct of the phenomenon in question; - connecting the limits and training ability of the individual. I conclude by reminding that saying more does not necessarily mean complicating things, very often the result is a progressive simplification. All journeys have a starting point, a path to follow and a destination. The same applies to training, and to its definition, you try to define it, you pursue it, you reach it, but you are never entirely satisfied with it.